2009
DOI: 10.1108/14779960910955909
|View full text |Cite
|
Sign up to set email alerts
|

Are socially exclusive values embedded in the avatar creation interfaces of MMORPGs?

Abstract: PurposeThe purpose of this paper is to show how both the presentation and limitation of visual choices in massively multiplayer online role‐playing games (MMORPG) avatar creation interfaces tends to exclude or favor different real life social groups.Design/methodology/approachA novel method combining both quantitative and critical analysis of the syntagmatic‐paradigmatic structure of MMORPG avatar creation interfaces is used to inform the findings of this study.FindingsThis study concludes that as cultural int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 17 publications
1
25
0
Order By: Relevance
“…A handful of studies have provided data in terms of interface analysis. Research conducted by Consalvo [5] and Pace et al [27,28] reported on quantifiable differences between different race and sex choices within games, illustrating how socially exclusive values (marginalization of minorities by making it impossible to create representative avatars) were coded within the games [28]. Data was collected by counting all of the distinct customization options available to players.…”
Section: Related Work 21 Analytical Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A handful of studies have provided data in terms of interface analysis. Research conducted by Consalvo [5] and Pace et al [27,28] reported on quantifiable differences between different race and sex choices within games, illustrating how socially exclusive values (marginalization of minorities by making it impossible to create representative avatars) were coded within the games [28]. Data was collected by counting all of the distinct customization options available to players.…”
Section: Related Work 21 Analytical Methodsmentioning
confidence: 99%
“…When creating an avatar, users are presented with hundreds, if not thousands of options to customize their avatar's appearance, for instance, selecting their avatar's hairstyle or skin colour. These options are made available in what are typically called avatar creation interfaces [28]. In many cases, these interfaces are capable of producing millions of unique permutations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This presents two ethical concerns: First, manipulating presentational factors to mislead audiences may be unethical, especially should it cause them to act against their own interests (MacDorman, Coram, Ho, & Patel, 2010). Second, ignoring the effects of presentational factors may be unethical if it renews stereotypes or promotes one group's values over the values of other groups (Brey, 1999;Pace, Houssian, & McArthur, 2009). The potential for misuse increases with the ease of creating realistic animations and distributing them widely.…”
mentioning
confidence: 99%
“…Often, these affordances constrain self-representation in such a way that it is impossible for users to create representative avatars. This phenomenon is commonly referred to as social exclusion (Pace et al 2009). Our research examines the tension between interface affordances and self-representational practices in digital games and social VWs.…”
Section: Introductionmentioning
confidence: 99%